2022
DOI: 10.36303/satnt.2021cosaami.20
|View full text |Cite
|
Sign up to set email alerts
|

Study of one-step and two-step quench and partition heat treatments on a medium carbon high silicon alloy using dilatometry

Abstract: This study evaluated the microstructural evolution in a medium carbon high silicon steel during one-step, and two-step quench and partition (Q&P) processes using dilatometry experiments. The two-step Q&P process was carried out using different quench temperatures ranging from 180 to 260 °C. In the one-step process, Q&P heat treatment samples were held isothermally for ten minutes after quenching at specified temperatures ranging between 200 and 4°50 C. The two-step Q&P process yielded a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The presence of RA should be tailored to achieve the desired mechanical properties of the final material. [6][7][8][9] Moreover, it must be noticed that, depending on the morphology and stability of austenitic particles, and on the surrounding microstructure, different strain-induced transformation kinetics are obtained, thus introducing different properties in the material. [10][11][12] Several studies have shown that the final properties obtained through this treatment, depending on the steel grade, can reach an UTS of 1600-2000 MPa associated with good values of elongation at break: these properties are not achieved with traditional quenching and tempering (QT) treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of RA should be tailored to achieve the desired mechanical properties of the final material. [6][7][8][9] Moreover, it must be noticed that, depending on the morphology and stability of austenitic particles, and on the surrounding microstructure, different strain-induced transformation kinetics are obtained, thus introducing different properties in the material. [10][11][12] Several studies have shown that the final properties obtained through this treatment, depending on the steel grade, can reach an UTS of 1600-2000 MPa associated with good values of elongation at break: these properties are not achieved with traditional quenching and tempering (QT) treatments.…”
Section: Introductionmentioning
confidence: 99%